Transformasi Digital dalam Manajemen Perkantoran untuk Meningkatkan Efisiensi dan Produktivitas Kerja - Yumarsono Muhyi (JURNAL ADMINISTRASI KANTOR, 2025)
Digital transformation has fundamentally changed the office management landscape, shifting conventional administrative practices toward an integrated, flexible, and data-driven work ecosystem. However, despite the accelerated adoption of technology, the human dimension at the center of every work process often receives less attention. This article examines how digital transformation in office management can improve work efficiency and productivity through a human-centered approach. This study uses a qualitative-descriptive approach with secondary data analysis from public sources, including the Ministry of Administrative and Bureaucratic Reform's SPBE Index, the UN E-Government Development Index report, and a literature review of Scopus journals for the 2020-2026 period. The analysis shows that digital transformation in office management contributes to increased process efficiency, data accuracy, and service speed. However, sustainable productivity is only achieved if the technological approach is accompanied by investments in employee digital competencies, adaptive leadership, and an inclusive work culture. A human-centered approach has proven to be a prerequisite for the success of meaningful and sustainable digital transformation. This article contributes to the development of a conceptual framework for humanistic and implementable digital office transformation for public and private organizations in Indonesia. Keywords: digital transformation, office management, work efficiency, productivity, human-centered